Managing indonesian language learning through digital applications to enhance storytelling skills in primary schools - Risma Yanti; Endang Komara (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyse the management of Indonesian learning based on digital applications in improving the storytelling skills of elementary school students. The focus of the study is directed at the implementation of the PDCA (Plan-Do-Check-Act) cycle which includes planning, implementation, evaluation, and follow-up of learning at SDN Palasari and SDN 2 Parungkuda. The research uses a qualitative approach with data collection techniques through observation, interviews, and documentation, which are then analysed descriptively. The results of the study show that both schools have integrated digital applications in learning with distinct characteristics. Teachers at SDN Palasari emphasize digital differentiation and innovation using applications such as Canva, Pixton, and Kahoot, while teachers at SDN 2 Parungkuda emphasize flexibility in dealing with limited facilities, by utilizing simple devices. These differences illustrate the variation in the level of TPACK mastery and the stages of technology adoption. In general, the application of digital applications has been proven to support improving students' storytelling skills while instilling character values. These results are in line with the findings of previous research on the effectiveness of digital storytelling, but this study presents a new contribution by placing digital applications within a systematic and sustainable learning management framework. Thus, this study emphasizes that the integration of digital applications is not just the use of media, but a measurable, consistent, and oriented learning management strategy that is oriented towards continuous quality improvement in elementary schools.